2020
DOI: 10.1158/1078-0432.ccr-20-1497
|View full text |Cite
|
Sign up to set email alerts
|

Copy-Number Alteration Burden Differentially Impacts Immune Profiles and Molecular Features of Hepatocellular Carcinoma

Abstract: Background and Aims: Chromosomal instability is a hallmark of cancer that results in broad and focal copy number alterations (CNAs), two events associated with distinct molecular, immunological and clinical features. In hepatocellular carcinoma (HCC) the CNAs role has not been thoroughly assessed. Thus, we dissected the impact of CNA burdens on HCC molecular and immune features. Methods: We analyzed SNP-array data from 452 paired tumor/adjacent resected HCCs and 25 dysplastic nodules. For each sample, broad an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 60 publications
(90 reference statements)
7
27
0
Order By: Relevance
“…In addition, we further investigated the molecular features of tumors with low and high CNV risk scores, and the results showed that tumors with high CNV risk scores were characterized as highly malignant, as reflected by the TMB, MMB and CNI score. A recent study reported that HCC with high broad CNV score showed high mutational burdens, 35 which was similar to our study. In addition, this study indicated that patients with HCC with high broad CNV scores had lower ratio of observed/expected neo-antigens.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, we further investigated the molecular features of tumors with low and high CNV risk scores, and the results showed that tumors with high CNV risk scores were characterized as highly malignant, as reflected by the TMB, MMB and CNI score. A recent study reported that HCC with high broad CNV score showed high mutational burdens, 35 which was similar to our study. In addition, this study indicated that patients with HCC with high broad CNV scores had lower ratio of observed/expected neo-antigens.…”
Section: Discussionsupporting
confidence: 92%
“…[31][32][33][34] A recent study found that HCC tumors with a low burden of broad copy number chromosomal alterations display higher immune infiltration and have a better response rate to anti-PD-1 inhibitors than those with a median/high broad copy number. 35 Moreover, Davoli et al 31 found that a higher CNV burden in tumor tissue correlated with immune escape and poorer survival in patients with metastatic melanoma treated with immunotherapy. Regarding liquid biopsy, Weiss et al 36 constructed a CNI scoring system based on plasma cfDNA and found that the CNI score could be used as an early indicator of the response Open access to immunotherapy for diverse advanced cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tumor aneuploidy is likely to increase intratumor heterogeneity, which may inhibit tumor immunity ( 63 ). Many solid cancers presenting with a high somatic copy alteration burden exhibit features of immune exclusion, whereas tumors displaying low rates of aneuploidy present an immune active profile ( 26 , 27 , 64 ). High-level SCNAs are classified through bioinformatic approaches as events where focal copy number gain (or loss) are higher (or lower) than the maximum (or minimum) median arm-level copy number gain (or loss), hence avoiding artifacts or false positives after comparison with low-level SCNAs linked to the ploidy of tumor samples and thus obtaining more reliable thresholds ( 65 , 66 ).…”
Section: Genetic Instabilitymentioning
confidence: 99%
“…Aneuploidy, the harboring of an abnormal number of chromosomes, in several tumors has been reported as a predictive biomarker for efficacy of immune checkpoint inhibitor (78). A recently conducted study on the relationship between copy number alterations (CNAs) and immune profiles of HCC, found that higher levels of broad CNAs resulting from aneuploidy show less immune-cell infiltration and are regarded as the primary reason for resistance to immune therapy (79). This CNAs and immune-phenotype relationship was seen in dysplastic nodules and early HCC.…”
Section: Future Perspectives: Towards the Stage Of Immunotherapymentioning
confidence: 99%